NANOMEDICINE DRUG DELIVERY SYSTEM FOR BRAIN DISEASES - THOTA NEELIMA, (International Journal of Pharma and Bio Sciences, 2015)
Brain is the control center of the body. It controls each and every stimulus in the body. Disease is an impairment of health or a condition of abnormal functioning of our body. The cause of disease is either external like infectious diseases may be an internal disease such as auto immune diseases. Some of these are fatal. There are many deadliest diseases in human one among them is Brain diseases, with this whole body control system gets affected. There are many therapies in practice, but they control the progress of the disease rather than cure. A new technique in nanotechnology in the field of medicine is Nanomedicine. Nanomedicine therapy showed immense results in curing as well as imaging various diseases along with Brain diseases. The main aim of this review article is to provide the information to the researchers about the scientific works done on some of the brain diseases like Alzheimer’s disease, Cerebral palsy, epilepsy, multiple sclerosis, Parkinson’s using nanomedicine technique in a concise manner and to develop other potent drug delivery systems for imaging and curing of brain diseases as well as to include new tests and testing guidelines.